Effect of two annealing processes on the thermal regeneration of fiber Bragg gratings in hydrogenated standard optical fibers - Lu, Kai; Yang, Hangzhou; Lim, Kok Sing; Ahmad, Harith; Zhang, Pan; Tian, Qin; Ding, Xiangzi; Qiao, Xueguang (Optical Society of America, 2018)
In this work, we demonstrate the thermal regeneration of fiber Bragg gratings written in the hydrogenated standard communication optical fibers by two annealing processes. The first annealing process is done at an intermediate temperature (500°C, 700°C, and 900°C) for a specific period of time before cooling down to room temperature. The second annealing is at 1000°C in which the thermal regeneration is attained. The experimental results show that the regenerated gratings that are preannealed at 700°C have charted a reflectivity larger than 65%. They have higher thermal stability compared to that of the standard annealing process. Meanwhile the difference in temperature sensitivity is very small. The temperature sensitivities of regenerated gratings, which have undergone only two annealing processes, are 16.1 pm/°C and 15.8 pm/°C, respectively.